Dialogue interreligieux et dialogue œcuménique, différences et similitudes - Thom Sicking (Chrétiens et Sociétés, 2005)
Interreligious dialogue, between several religious traditions, is different from the ecumenical dialogue. Ecumenism aims at overcoming the division among the churches. Both dialogs develop recently, because of the confrontation between the religions. It needs the ability of the partners engaged in such an endeavour. But it is also necessary to take into account the various situations: debates between theologians, between religious leaders or between ordinary people in the daily life.